Fungsi Budgetary dan Regulatory Penerimaan Negara Bukan Pajak (PNBP) di Indonesia - Tinton Ditisrama Ditisrama; Ramlani Lina Sinaulan; Ismail Ismail Ismail (Syntax Idea)
Non-Tax Revenue (PNBP) is one of the instruments of state revenue excluding tax revenues, and grants are the second largest contributor to revenue after tax revenues in the APBN. Similar to tax revenues, the constitutionality of PNBP is also regulated in Article 23A of the 1945 Constitution of the Republic of Indonesia. Furthermore, the legal politics of the constitutionality of PNBP is described in Law Number 9 of 2018 concerning PNBP. In principle, PNBP has two functions, namely the budgetary function and the regulatory function. The two functions of PNBP are the spirit or soul of PNBP, meaning that both functions must be ensured that they really work and synergize with each other, without this, the existence of PNBP in supporting state/government activities in order to achieve people's welfare will be insignificant and not strategic. The method used in this study is juridical-normative, with this method the author tries to explain how the implementation of the budgetary function and the regulatory function of PNBP in supporting the implementation of state/government activities in Indonesia.